Coaching and 'Self-repair': Examining the 'Artful Practices' of Coaching Work. (June 2023) - Corsby, Charles L T; Jones, Robyn L; Thomas, Gethin Ll; Edwards, Christian N
The significance of this article lies in examining how sports coaches construct and negotiate their professional sense making; what Goffman described as the practices engaged in to manage 'ugly' interpretations. Using the work of Garfinkel and Goffman, the article pays attention to coaches' 'ethno-methods'; that is, the background knowledge and practical competency employed in forming and maintaining social order. In doing so, the explanatory accounts of Christian, a coach and author who supported the co-construction of this work, were collected via recorded interviews over the course of a 3-month period during a competitive season. The analysis explores the procedures used to 'achieve coherence' in what he did. The analysis employed Garfinkel's description of 'artful practices' and related concepts of 'self repair' to demonstrate the fundamental interactional 'work' done by Christian, not only to understand why he did what he did, but also how he would 'get things done' in future. Such analysis highlights the mundane routines of coaching in particular, and work settings in general, to reveal the backstage manufacturing individuals 'do' to maintain a sense of 'practical objectivity' to their continual inferences, judgements, and justifications of practice.